Surgical Anatomy of the Medial Sural Artery Perforator Flap - Wong, Man-Zhi; Wong, Chin-Ho; Tan, Bien-Keem; Chew, Khong-Yik; Tay, Shian-Chao (Journal of Reconstructive Microsurgery, 2012)
Background The medial sural (medial gastrocnemius) perforator flap is a thin flap with a long pedicle. It has tremendous potential for applications in a variety of soft-tissue defects. We aimed to further clarify the vascular anatomy of the medial sural region and establish a safe approach for elevation of this flap.Methods Ten fresh cadaveric lower limbs were injected and used in this study. We identified the locations and courses of the medial sural artery perforators and correlated them to anatomic landmarks.Results The medial sural artery divides into two branches, a medial and lateral branch. Correspondingly, musculocutaneous perforators supplying the overlying skin were oriented in two parallel vertical rows, along the course of the lateral or medial branch of the medial sural artery. Two to six perforators were located 6 cm to 22.5 cm from the popliteal crease. Perforators from the lateral row, nearer the posterior midline, were generally larger. In most cases, a large perforator with a superficial, straight intramuscular course could be identified a mean of 10 cm distal to the popliteal crease and an average of 2 cm from the posterior midline. Based on the above findings, we successfully used this flap in five clinical cases.Conclusion Perforators of the medial sural artery were arranged in a medial and a lateral row. Use of perforators from the lateral row, nearer the posterior midline, is preferable as these are usually larger in size. A consistent major perforator could always be identified in all specimens. With increased safety and confidence in flap harvesting, the medial sural artery perforator flap may find wider clinical applications.Clinical question: TherapeuticLevel of Evidence: IV
Keywords: cadaveric; anatomy; sural artery perforator flap; gastrocnemius muscle